Transport coefficients of He+ ions in helium - Viehland, Larry A.; Johnsen, Rainer; Gray, Benjamin R.; Wright, Timothy G. (American Institute of Physics, 2016)
Recent theoretical advances have made it possible to calculate ab initio interaction potentials for atomic ionatom collisions that are highly accurate, and to use the potentials to calculate gaseous ion transport coefficients that meet or exceed the accuracy with which they can be measured1-4. Hence gaseous ion transport data serve as stringent tests of the interaction potentials. Advances in the calculation of transport properties, unfortunately, have not included the situation where atomic ions move through their parent gases, where resonant charge transfer (RCT) can occur. The purpose of this paper is to fill this void.